Analisis Sistem Implementasi Talent Acquisition Process terhadap karyawan kontrak perusahan konstruksi PT X di Batam - Farah Fakhirah Suganda; Yuli Indah Fajar Dini (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The purpose of this research is to find out the suitability of the implementation of the talent acquisition process system procedure at the construction company PT X in Batam with the standards used, namely based on the law and to study directly the company's procedures in carrying out the talent acquisition process system, both from looking for candidates, conducting interviews, training up to the hiring stage. Data collection techniques used interviews with PT X Talent Acquisition staff, observation and documentation. The procedures of the talent acquisition process system that will be observed and analyzed are Sourcing and Lead Generation, Recruiting and Attracting, Interviewing and Assessing, Checking References, Making Final Selections, Hiring and Onboarding. The results obtained after implementation are a hiring system that complies with regular procedures and produces qualified candidates at every stage of the process that is passed, the author can study and assist in each process, such as contacting candidates at each stage of the process, helping prepare candidate documents, helping prepare candidate needs for tests. Making it easier for Talent Acquisition staff in the process of carrying out each procedure of the talent acquisition process system.